Համընդհանուրի և ազգայինի դրսևորումները իսպանական հրաշապատում հեքիաթներում - Հ. Գ. Բաղդասարյան; Զ. Ռ. Ազիզբեկյան (ՀՀ ԳԱԱ հրատ.)
Сказки любого народа отличаются своеобразием формы и содержания, но при этом они имеют некую тематическую общность и связаны с древними ритуалами, легендами, религиозными представлениями и, в целом, с архетипами человеческого сознания. Fairy tales of every nation are distinguished by the peculiarity of their form and content, but at the same time they show a great deal of thematic commonalities and are connected to ancient rituals, myths, religious perceptions, and to archetypes of human thinking in general.
Keywords: Geography; Anthropology; Recreation; Philology; Linguistics; Language and Literature; Folklore; Literature